Pengaruh Quizizz terhadap Hasil Belajar Teori Pelajaran Produktif Siswa Otomotif di SMK Negeri 1 Muarabatu - Islami Fatwa; Taufiq Taufiq (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This research stemmed from the ineffectiveness of teaching theory in automotive productivity lessons. Traditional methods were used, resulting in suboptimal student outcomes. This suggests the need for new learning approaches, such as game-based digital assessments. This approach aligns with the characteristics of vocational schools and the needs of 21st-century learning. The purpose of this research was to determine the influence of the Quizizz platform on the theoretical learning outcomes of automotive students at SMK Negeri 1 Muarabatu. This research employed a quantitative method with a one-group pretest-posttest pre-experimental design. Thirty eleventh-grade Automotive Engineering students participated. Data were collected using standardized tests before and after using Quizizz. The data were then analyzed using paired-sample t-tests using statistical software. The analysis showed an increase in students' average score from 62.40 (pretest) to 82.10 (posttest). The statistical test showed a t-value of 9.27 with a significance of p < 0.05. This indicates a significant difference between learning outcomes before and after using Quizizz. These results demonstrate that Quizizz has a positive and significant impact on improving theoretical learning outcomes in automotive productivity courses. From an educational perspective, these research findings underscore the importance of developing digital learning with interactive assessments. The goal is to make students more active, motivated, and improve their learning outcomes. This aligns with vocational education, which keeps pace with technological developments and 21st-century learning needs.